2021
DOI: 10.1371/journal.pone.0250706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on suicide and self-harm among patients presenting to the emergency department of a teaching hospital in Nepal

Abstract: The COVID-19 pandemic is a global challenge that is not just limited to the physical consequences but also a significant degree of a mental health crisis. Self-harm and suicide are its extreme effects. We aim to explore the impact of this pandemic on suicide and self-harm in our Emergency Department. A cross-sectional study was conducted including all fatal and nonfatal self-harm patients presenting to the emergency department during the lockdown period (March 24-June 23, 2020; Period1), matching periods in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 20 publications
4
39
0
1
Order By: Relevance
“…Other studies have also reported a COVID-19 pandemic-related increase in suicide in some parts of South Asia [ 31 , 32 ]. Our results are also consistent with the report of increased suicide and self-harm cases during the COVID-19 pandemic in one of the biggest teaching hospitals in Nepal [ 33 ]. Our results are different from a study that suggests the suicide rates have not increased during the COVID-19 pandemic in some high-income countries [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also reported a COVID-19 pandemic-related increase in suicide in some parts of South Asia [ 31 , 32 ]. Our results are also consistent with the report of increased suicide and self-harm cases during the COVID-19 pandemic in one of the biggest teaching hospitals in Nepal [ 33 ]. Our results are different from a study that suggests the suicide rates have not increased during the COVID-19 pandemic in some high-income countries [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the study carried out in the neighbouring country of Nepal in early 2020 by Shrestha et al, 2021 which demonstrated a 44% increase in self harm attempts along with increased admissions and increase in in-hospital mortality [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The multifactorial manner in which COVID-19 engulfs our lives via massive the lockdowns and the fear of death induces such a damaging cycle to the mental health of all. One such nation who seems to be particular hard hit by both COVID-19 and the mental health implications thereof is the mountainous country of Nepal [8]. Every year, around 700,000 people die by suicide globally.…”
Section: Mental Health and Covid-19mentioning
confidence: 99%
“…The importance of this study is multifaceted as it both shows the negative effect of COVID-19 on mental and simultaneously exposes the hidden dimension of looming poor mental health circulating within the country. This subsurface level of poor mental health has been exposed through the precipitating factor of COVID-19 [8]. Further research into the suicidality and current impact of COVID-19 on the mental health of those in Nepal conducted by Acharya SR, et al has highlighted the significant and dire situation that Nepal is facing as an average of 18 suicides a day occurred throughout the lockdown period.…”
Section: Nepalese Mental Health During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation